A review of entrepreneurship education research and practice - Sendra-Pons, Pau; Calatayud, Carolina; Garzón, Dolores (Journal of Management and Business Education, 2022)
Entrepreneurship has increasingly captured policymaker’s attention due to the need to promote economic development and job creation. Among the drivers of entrepreneurship, entrepreneurial education is of particular significance. This paper reviews entrepreneurship education from a research and practice perspective. Firstly, a discussion is held as to whether entrepreneurial talent is born or bred. Secondly, the different approaches to entrepreneurship education are revised, specifying their distinctive characteristics. This is followed by a review of research on the potential of entrepreneurship education to awaken individuals’ entrepreneurial intentions. Finally, a series of practical considerations aimed at improving entrepreneurship education programs are proposed. Ultimately, this paper contextualizes entrepreneurship education, advocating its relevance in the promotion of entrepreneurial activity.